Improvements of blood pressure, heart rate, and pulse pressure in men with hypogonadism and type 2 diabetes, with and without long-term testosterone therapy. (14th October 2021) - Saad, F; Haider, A; Haider, K S; Doros, G; Traish, A
Abstract: Introduction: Guidelines by the ESC and EASD recommend that patients with hypertension and type 2 diabetes (T2DM) are treated individually to a systolic blood pressure (SBP) target of <130 mmHg. There is little information in the literature about effects of testosterone therapy on blood pressure in men with hypogonadism and T2DM. Methods: In a registry of men with hypogonadism in a urological office, 361 men had T2DM and received standard diabetes treatment including lifestyle recommendations and coaching in a diabetes center. 183 men received TTh with testosterone undecanoate injections 1000 mg/12 weeks following an initial 6-week interval (T-group). 178 men opted against TTh and served as controls (CTRL). Changes over time between groups were compared and adjusted for age, weight, waist circumference, fasting glucose, blood pressure, lipids and quality of life to account for baseline differences between the two groups. 12-year analyses of 3149 patient-years are reported. Results: Mean (median) follow-up 8.2±3.2 (8) years in the T-group, 9.2±2.8 (10) years in CTRL, baseline age: 60.6±5.4 (T-group) and 63.5±5.0 (CTRL) years (p<0.0001). All but 7 patients were overweight or obese. All but 4 patients (97.8%) in the T-group and all but 26 (85.4%) in CTRL had hypertension, defined by SBP ≥130 and/or DBP ≥85 mmHg. Baseline SBP in the T-group was 163.0±13.5, in CTRL 145.6±14.6 mmHg. SBP decreased in the T-group by 33.1±1.2 and increased in CTRL by 18.3±1.2 mmHg, estimated adjusted difference between groups at 12 years: −51.5 mmHg [95% CI: −55.4; −47.6] (p<0.0001 for all). The unadjusted mean SBP after 12 years was 130.2±6.5 mmHg in the T-group and 158.3±15.1 mmHg in CTRL. Baseline DBP in the T-group was 97.4±10.9, in CTRL 84.8±10.3 mmHg. DBP decreased in the T-group by 20.3±0.9 and increased in CTRL by 12.5±0.9 mmHg, estimated adjusted difference between groups at 12 years: −32.8 mmHg [95% CI: −35.7; −29.9] (p<0.0001 for all). The unadjusted mean DBP after 12 years was 75.4±3.3 mmHg in the T-group and 94.3±8.9 mmHg in CTRL. Heart rate decreased in the T-group by 3.8±0.5 bpm and increased in CTRL by 2.3±0.5 bpm, estimated adjusted difference between groups at 12 years: −6.0 bpm [95% CI: −7.6; −4.5] (p<0.0001 for all). Pulse pressure, a surrogate for arterial stiffness, decreased in the T-group by 12.8±0.8 and increased in CTRL by 5.9±0.8, estimated adjusted difference between groups at 12 years: −18.7 [95% CI: −21.1; −16.3] (p<0.0001 for all). Men in the T-group lost 19.7±0.4% weight, men in CTRL gained 9.1±0.4%, estimated adjusted difference: −28.8% [95% CI: −30.2;-27.4] (p<0.0001 for all). Medication adherence to testosterone was 100% as all injections were administered in the medical office and documented. Conclusions: Long-term treatment with testosterone in men with hypogonadism, T2DM and hypertension reduced systolic and diastolic blood pressure, heart rate, and pulse pressure, compared to untreated controls. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer AG